Barn Owl pellets (Aves: Tyto furcata) reveal a higher mammalian richness in the Restinga de Jurubatiba National Park, Southeastern Brazil - Lemos, Hudson de Macedo; Silva, Carina Azevedo Oliveira; Patiu, Fabio de Mello; Gonçalves, Pablo Rodrigues (Biota Neotropica, 2015)
The northern coast of the state of Rio de Janeiro harbors the largest coastal sandy plains (restingas) of southeastern Brazil, severely threatened due to recent human occupation. In this context, mammal inventories becomes urgent to support biodiversity conservation and management policies. This paper aims to update the knowledge on the mammalian species richness of Restinga de Jurubatiba National Park by analyzing pellets of the Barn owl Tyto furcata. The analyses of 4745 mammalian bone fragments (1739 individuals) revealed the occurrence of 17 species belonging to the orders Rodentia (9 spp.), Didelphimorphia (2 spp.) and Chiroptera (6 spp.). The rodents Mus musculus and Cerradomys goytaca accounted for 77.2% of the total individuals preyed, suggesting that the Barn owl hunts in both disturbed and natural open shrub formations. A compilation of previous records, together with those provided in the present study, indicates the occurrence of 44 species of mammals in the Restinga de Jurubatiba National Park, of which six (13.6%) were exclusively detected in pellets. These new records include species adapted to open formations of the interior of Brazil that were not previously reported in restingas on the basis of voucher-specimens, such as the rodents Necromys lasiurus and Calomys tener, the latter being recorded for the first time in the littoral of Rio de Janeiro state. This study underscores the importance of owl pellet analysis as a complementary and indispensable method for inventorying mammals. The results highlight the Restinga de Jurubatiba National Park as one of the restingas in Southeastern Brazil with the highest number of mammal species.